Nobel Lecture: Institutions, Technology, and Prosperity - Acemoglu, Daron (American Economic Review, 2025)
This paper reviews the main motivations and arguments of my work on comparative development, colonialism, and institutional change, which was often carried out jointly with James Robinson and Simon Johnson. I then provide a simple framework to organize these ideas and connect them with my research on innovation and technology. The framework is centered around a utility-technology possibilities frontier, which delineates the possible distributions of resources in a society both for given technology and working via different technological choices. It highlights how various types of institutions, market structures, norms, and ideologies influence moves along the frontier and shifts of the frontier, and it provides a simple formalization of the social forces that lead to institutional persistence and those that can trigger institutional change. The framework also enables us to conceptualize how, during periods of disruption, existing—and sometimes quite small—differences can have amplified effects on prosperity and institutional trajectories. In this way, it suggests some parallels between different disruptive periods, including the onset of European colonialism, the spread (or lack thereof) of industrial technologies in the nineteenth century, and decisions related to the use, adoption, and development of AI today. (JEL D02, D72, E23, F54, O43)